Mitochondria and calcium signaling in cell life and cell death - Duchen, Michael R. (Henry Stewart Talks, 2018)
Calcium signalling, ubiquitous and associated with increased energy demand, Mitochondria machinery to for taking up calcium from the cytosol, The transfer of calcium from cytosol to mitochondria (stimulation of oxidative phosphorylation & matching energy supply with demand), Mutations in proteins that regulate mitochondrial calcium uptake (causation of a neuromuscular disease, possibly by mitochondrial calcium overload), Acute severe calcium overload causes cell death during reperfusion of ischaemic tissues, The permeability transition pore, a potential therapeutic target